2014
DOI: 10.5657/kfas.2014.0945
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Distribution of Trammel Net Catches in the Coastal Waters of Gangwon Province, Korea

Abstract: This study was conducted to provide basic data for optimal fisheries management through the accurate understanding the catches, fishing level, species composition, distribution characteristics and fisheries status of trammel net in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…In addition, the short length of the MiFish barcode may not be variable enough to discriminate between closely related species, especially in Pleuronectiformes or Scorpaeniformes, as reported in previous studies (Yamamoto et al, 2017). By contrast, Pseudopleuronectes herzensteini and Sebastes owstoni in those orders were accurately assigned only by FishU, which was supported by previous studies (Sohn et al, 2014;Lee and Kim, 2016). In addition to these two orders, two related species in each genus, Alcichthys alcicornis and Alcichthys elongatus and Maurolicus japonicus and Maurolicus muelleri, should be reexamined.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, the short length of the MiFish barcode may not be variable enough to discriminate between closely related species, especially in Pleuronectiformes or Scorpaeniformes, as reported in previous studies (Yamamoto et al, 2017). By contrast, Pseudopleuronectes herzensteini and Sebastes owstoni in those orders were accurately assigned only by FishU, which was supported by previous studies (Sohn et al, 2014;Lee and Kim, 2016). In addition to these two orders, two related species in each genus, Alcichthys alcicornis and Alcichthys elongatus and Maurolicus japonicus and Maurolicus muelleri, should be reexamined.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, haplotypes in the family Sebastidae by MiFish showed a 100% identity to multiple species, indicating the low resolution of the MiFish region to distinguish those taxa ( Figure 5B), which was also identified in a previous study (Yamamoto et al, 2017). In contrast, two sebastids, Sebastes owstoni and Sebastiscus marmoratus, were clearly assigned by FishU with 99% identity to the database (Figure 5A), which was supported by a previous conventional survey (Sohn et al, 2014). In addition, the assignment of species in Pleuronectidae were highly different between MiFish and FishU.…”
Section: Design Of Fish-specific Universal Primer Fishusupporting
confidence: 82%
“…Similarly, off the eastern coast of Korea, some species such as G. stelleri and C. pinetorum move from nearshore waters into a deeper shelf and/or more offshore waters as they grow (Lee 2011). In general, seasonal fluctuations in fish composition and abundance are attributable to sequential patterns of migration and emigration by several species, and may be a feature of fish communities off the eastern coast of the Korean peninsula (Lee 2011;Choi et al 2012;Kang et al 2014;Sohn et al 2014Sohn et al , 2015.…”
Section: Community Characteristics Of Fish Assemblagesmentioning
confidence: 99%
“…All fish species studied were caught off the coast of Jumunjin (Table 1), where more than 77 fish species can be found (Yang et al, 2012;Lee et al, 2013;Sohn et al, 2014); all were caught on the morning of the sampling day. The Korea Ocean Observing and Forecasting System reported that the average temperature of surface seawater in the Jumunjin area 1 week before and 1 week after the date of purchase was about 9°C, well above the freezing point of seawater (http://sms.khoa.go.kr/koofs/eng/observation/obs_real_map.…”
Section: Thermal Hysteresismentioning
confidence: 99%